Factors influencing knowledge of postpartum mothers about baby blues in desmawati clinic Pancur Batu district, district Deli Serdang year 2020 - Siti Nurmawan Sinaga (Institute of Computer Science (IOCS), 2022)
Birth occurs naturally, draining the mother's energy and emotions. This is very tiring which affects the psychology of postpartum mothers. Baby Blues or new mother syndrome which is a mild emotional disturbance that appears in the first week after giving birth with symptoms such as anxiety, irritability, sleep disturbances and appetite. More than 80% of postpartum mothers experience baby blues, especially primiparous mothers, around 83%. If this is left unchecked, it will have a negative impact on the mother and the bab. This type of research is analytic descriptive with a cross sectional study approach. The population was all postpartum mothers who were breastfeeding as many as 35 postpartum mothers at the Desmawati Clinic Jln Pipa No.3, Lama Village, Pancur Batu District, Deli Serdang Regency, North Sumatra Province. This research uses total sampling. The total sampling technique, namely sampling, was carried out by taking all respondents from postpartum mothers. The number of samples used was 35 people. Data analysis technique using chi square. The results obtained in this study were based on the knowledge of postpartum mothers about baby blues based on age, using the Chi-Square Test showing Asymp. Sig. 0.152 <0.05) So the conclusion is H0 is accepted which means there is no significant relationship between age and knowledge of postpartum mothers about baby blues, based on parity, indicating Asymp. Sig. 0.192 <0.05) So the conclusion is H0 is accepted, which means there is no significant relationship between parity and postpartum mothers' knowledge about baby blues at the Desmawati Clinic in 2020, based on education showing Asymp. Sig. 0.001 <0.05) So the conclusion is H0 is accepted which means there is no significant correlation between education and postpartum mothers' knowledge about baby blues at Desmawati Clinic in 2020. There is no significant correlation between age, parity and education with the knowledge of postpartum mothers regarding knowledge of baby blues at the Desmawati Clinic in 2020